2018
DOI: 10.1093/jcr/ucy079
|View full text |Cite
|
Sign up to set email alerts
|

The Pleasure of Assessing and Expressing Our Likes and Dislikes

Abstract: Although consumer behavior theory has traditionally regarded evaluations as instrumental to consumer choice, in reality consumers often assess and express what they like and dislike even when there is no decision at stake. Why are consumers so eager to express their evaluations when there is no ostensible purpose for doing so? In this research, we advance the thesis that this is because consumers derive an inherent pleasure from assessing and expressing their likes and dislikes. In support of this thesis, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…Kang and Gretzel (2012) showed that tourists’ on-site experience sharing via a podcast enhances overall tourist experiences through perceived social presence and meaningfulness. He, Melumad, and Pham (2019) also showed that expressing and externalizing one’s momentary evaluation in consumption contexts provides tourists with hedonic benefits. That is, leisure travelers may feel an instant pleasure by expressing their feelings and opinions about their travel experiences.…”
Section: Conceptual Developmentmentioning
confidence: 96%
“…Kang and Gretzel (2012) showed that tourists’ on-site experience sharing via a podcast enhances overall tourist experiences through perceived social presence and meaningfulness. He, Melumad, and Pham (2019) also showed that expressing and externalizing one’s momentary evaluation in consumption contexts provides tourists with hedonic benefits. That is, leisure travelers may feel an instant pleasure by expressing their feelings and opinions about their travel experiences.…”
Section: Conceptual Developmentmentioning
confidence: 96%
“…Firms may further benefit from facilitating user posting of experiences on social media for social signaling, and from soliciting user feedback. Vacationers may feel greater attachment to a rental after sharing pictures of it, or after expressing their values by writing a review of the home (He, Melumad, and Pham 2018).…”
Section: Opportunities To Preserve Psychological Ownershipmentioning
confidence: 99%
“…Participants were recruited using Prolific, which is a crowdworking platform similar to Amazon MTurk, but designed specifically for academic research purposes. All participants were compensated F I G U R E 1 Theoretical framework employed in this study [Colour figure can be viewed at wileyonlinelibrary.com] for their time according to an estimation of the duration of their participation (He, Melumad, & Pham, 2018;Koepsell, 2017).…”
Section: Participantsmentioning
confidence: 99%